Association of Increased Levels of Homocysteine and Peripheral Arterial Disease in a Japanese-Brazilian Population - Garofolo, L.; Barros, N.; Miranda, F.; D'Almeida, V.; Cardien, L.C.; Ferreira, S.R. (European journal of vascular and endovascular surgery, 2007)
Our aim was to evaluate the possible association between homocysteine levels and peripheral arterial disease (PAD) in a population-based study of Japanese-Brazilians. This cross-sectional study was derived from a population-based survey on the prevalence of diabetes and associated diseases conducted in Japanese-Brazilians. A total of 1330 male and female subjects aged ≥ 30 years were submitted to clinical examination and laboratory procedures including homocysteine measurement. The ankle-brachial index (ABI) was calculated; subjects with ABI values <0.9 were diagnosed with PAD. The evaluable population included 1008 subjects. Logistic regression was used taking PAD as the dependent variable. Mean age of the population was 56.5 years and overall prevalence of PAD was 20%. A worse cardiovascular profile was found in male patients, including significantly higher homocysteine levels (11.9 ± 1.8 vs. 9.1 ± 1.1 μmol/L, p < 0.001). Men with PAD had higher prevalence rates of hyperhomocysteinemia compared to women (22.7% vs 7.6%). Univariate analysis showed an odds ratio of hyperhomocysteinemia for PAD of 1.51 [1.02–2.25] in men and 1.69 [1.06–2.68] in women. After adjustment for other cardiovascular risk factors, higher levels of homocysteine were only significantly related to PAD in men. In a Japanese-Brazilian population, elevated levels of homocysteine are associated with PAD in men. Prospective studies are necessary to confirm this finding.